1991
DOI: 10.1029/91gl02307
|View full text |Cite
|
Sign up to set email alerts
|

The role of corotating interaction regions in cosmic‐ray modulation

Abstract: We present the first global simulations of the modulation of galactic cosmic rays by a three‐dimensional solar wind with corotating interaction regions. The cosmic‐ray transport equation is solved in a computed wind and magnetic‐field model. The results show both the previously‐neglected small‐scale response to CIR's and global, drift‐dominated, effects which are similar to previous models. Our model predicts a correlation between the local magnetic field and the rate of decrease of the cosmic‐ray intensity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 13 publications
3
43
2
Order By: Relevance
“…Richardson et al (1996) pointed out that the SWD speed might be the most important parameter, favoring a diffusion-convection model for this behavior. On the other hand, Čalogović et al (2009) found a statistically significant correlation between the depression amplitude and the SWD magnetic field strength, which is more in favor of the diffusiondrift model proposed by Kota & Jokipii (1991). Similar inconsistencies were found in studies of ICMEs.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Richardson et al (1996) pointed out that the SWD speed might be the most important parameter, favoring a diffusion-convection model for this behavior. On the other hand, Čalogović et al (2009) found a statistically significant correlation between the depression amplitude and the SWD magnetic field strength, which is more in favor of the diffusiondrift model proposed by Kota & Jokipii (1991). Similar inconsistencies were found in studies of ICMEs.…”
Section: Introductionmentioning
confidence: 68%
“…It opposes modeling based on the propagating region of the enhanced scattering and reduced drift (Kota & Jokipii 1991) or enhanced convection , since no correlations were found between the amplitude of the depression and magnetic field strength/fluctuations/speed. But the time profile of SWDs, which we found to be very important for CR exclusion in general, was not regarded within these models.…”
Section: Influence Of Different Solar Wind Disturbances On Cosmic Raymentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the role of different ranges of the heliolongitudinal changes of the solar wind velocity in the A>0 and A<0 epochs was not considered. The 3-D models with heliolongitudinal dependent solar wind velocity with consequent changes of the frozen interplanetary magnetic field (IMF) were presented by Kota and Jokipii (1991; followed after the first 3-D model (Kota and Jokipii, 1983). Model of Kota and Jokipii (1991) was the first global simulations of the modulation of GCR by 3-D solar wind with corotating interaction regions (CIR), though there was not considered an expected difference of the amplitudes of the 27-day variations of the GCR intensity in the A>0 and A<0 polarity epochs.…”
Section: Introductionmentioning
confidence: 99%
“…The 3-D models with heliolongitudinal dependent solar wind velocity with consequent changes of the frozen interplanetary magnetic field (IMF) were presented by Kota and Jokipii (1991; followed after the first 3-D model (Kota and Jokipii, 1983). Model of Kota and Jokipii (1991) was the first global simulations of the modulation of GCR by 3-D solar wind with corotating interaction regions (CIR), though there was not considered an expected difference of the amplitudes of the 27-day variations of the GCR intensity in the A>0 and A<0 polarity epochs. Later, Kota and Jokipii (2001) developed new time dependent 3-D model including multiple heliospheric neutral sheet (HNS) characterizing high solar activity to cover more complex structures of the HNS and CIRs.…”
Section: Introductionmentioning
confidence: 99%